Стохастичний резонанс у цифровому фільтрі - Шаповал, І. Р. (ХНУРЕ, 2025)
Stochastic resonance has been attracting the attention of both physicists and electronics specialists for the past two decades. This phenomenon occurs when the presence of both a useful signal (usually harmonic) and noise in a nonlinear system leads to an increase in the signal-to-noise ratio at the system output when the input noise level increases within certain limits. The paper considers stochastic resonance in a radio engineering system similar to a digital filter based on the Lyapunov characteristic function. The physical nature of the stochastic resonance is investigated and its existence in a radio engineering system is confirmed by modeling.
Keywords: стохастичний резонанс; цифровий фільтр